Prognostic Value of Elevated Levels of Plasma N-Acetylneuraminic Acid in Patients With Heart Failure. (November 2021) - Li, Chenze; Zhao, Mingming; Xiao, Lei; Wei, Haoran; Wen, Zheng; Hu, Dong; Yu, Bo; Sun, Yang; Gao, Jianing; Shen, Xiaoqing; Zhang, Qi; Cao, Huanhuan; et al.
Abstract : Background: Cardiac sialylation is involved in a variety of physiological processes in the heart. Altered sialylation has been implicated in heart failure (HF) mice. However, its role in patients with HF is unclear, and the potential effect of modulation of cardiac sialylation is worth exploring. Methods: We first assessed the association between plasma N-acetylneuraminic acid levels and the incidence of adverse cardiovascular events in patients with HF over a median follow-up period of 2 years. Next, immunoblot analysis and lectin histochemistry were performed in cardiac tissue to determine the expression levels of neuraminidases and the extent of cardiac desialylation. Finally, the therapeutic impact of a neuraminidase inhibitor was evaluated in animal models of HF. Results: Among 1699 patients with HF, 464 (27%) died of cardiovascular-related deaths or underwent heart transplantation. We found that the elevated plasma N-acetylneuraminic acid level was independently associated with a higher risk of incident cardiovascular death and heart transplantation (third tertile adjusted hazard ratio, 2.11 [95% CI, 1.67–2.66], P <0.001). In addition, in cardiac tissues from patients with HF, neuraminidase expression was upregulated, accompanied by desialylation. Treatment with oseltamivir, a neuraminidase inhibitor, in HF mice infused with isoproterenol and angiotensin II significantly inhibited desialylation and ameliorated cardiac dysfunction. Conclusions: This study uncovered a significant association between elevated plasma N-acetylneuraminic acid level and an increased risk of a poor clinical outcome in patients with HF. Our data support the notion that desialylation represents an important contributor to the progression of HF, and neuraminidase inhibition may be a potential therapeutic strategy for HF. Abstract : Supplemental Digital Content is available in the text.